Increased Reactive Oxygen Species–Mediated Ca2+/Calmodulin-Dependent Protein Kinase II Activation Contributes to Calcium Handling Abnormalities and Impaired Contraction in Barth Syndrome. Issue 19 (11th May 2021) - Liu, Xujie; Wang, Suya; Guo, Xiaoling; Li, Yifei; Ogurlu, Roza; Lu, Fujian; Prondzynski, Maksymilian; de la Serna Buzon, Sofia; Ma, Qing; Zhang, Donghui; Wang, Gang; Cotton, Justin; et al.
Abstract : Background: Mutations in tafazzin ( TAZ ), a gene required for biogenesis of cardiolipin, the signature phospholipid of the inner mitochondrial membrane, causes Barth syndrome (BTHS). Cardiomyopathy and risk of sudden cardiac death are prominent features of BTHS, but the mechanisms by which impaired cardiolipin biogenesis causes cardiac muscle weakness and arrhythmia are poorly understood. Methods: We performed in vivo electrophysiology to define arrhythmia vulnerability in cardiac-specific TAZ knockout mice. Using cardiomyocytes derived from human induced pluripotent stem cells and cardiac-specific TAZ knockout mice as model systems, we investigated the effect of TAZ inactivation on Ca 2+ handling. Through genome editing and pharmacology, we defined a molecular link between TAZ mutation and abnormal Ca 2+ handling and contractility. Results: A subset of mice with cardiac-specific TAZ inactivation developed arrhythmias, including bidirectional ventricular tachycardia, atrial tachycardia, and complete atrioventricular block. Compared with wild-type controls, BTHS-induced pluripotent stem cell–derived cardiomyocytes had increased diastolic Ca 2+ and decreased Ca 2+ transient amplitude. BTHS-induced pluripotent stem cell–derived cardiomyocytes had higher levels of mitochondrial and cellular reactive oxygen species than wild-type controls, which activated CaMKII (Ca 2+ /calmodulin-dependent protein kinase II). Activated CaMKII phosphorylated the RYR2 (ryanodine receptor 2) on serine 2814, increasing Ca 2+ leak through RYR2. Inhibition of this reactive oxygen species–CaMKII–RYR2 pathway through pharmacological inhibitors or genome editing normalized aberrant Ca 2+ handling in BTHS-induced pluripotent stem cell–derived cardiomyocytes and improved their contractile function. Murine Taz knockout cardiomyocytes also exhibited elevated diastolic Ca 2+ and decreased Ca 2+ transient amplitude. These abnormalities were ameliorated by Ca 2+ /calmodulin-dependent protein kinase II or reactive oxygen species inhibition. Conclusions: This study identified a molecular pathway that links TAZ mutation with abnormal Ca 2+ handling and decreased cardiomyocyte contractility. This pathway may offer therapeutic opportunities to treat BTHS and potentially other diseases with elevated mitochondrial reactive oxygen species production. Abstract : Supplemental Digital Content is available in the text.